Nicotinic acetylcholine receptors and learning and memory deficits in Neuroinflammatory diseases - Echeverria, Valentina; Mendoza, Cristhian; Iarkov, Alex (Frontiers in Neuroscience, 2023)
Animal survival depends on cognitive abilities such as learning and memory to adapt to environmental changes. Memory functions require an enhanced activity and connectivity of a particular arrangement of engram neurons, supported by the concerted action of neurons, glia, and vascular cells. The deterioration of the cholinergic system is a common occurrence in neurological conditions exacerbated by aging such as traumatic brain injury (TBI), posttraumatic stress disorder (PTSD), Alzheimer’s disease (AD), and Parkinson’s disease (PD). Cotinine is a cholinergic modulator with neuroprotective, antidepressant, anti-inflammatory, antioxidant, and memory-enhancing effects. Current evidence suggests Cotinine’s beneficial effects on cognition results from the positive modulation of the α7-nicotinic acetylcholine receptors (nAChRs) and the inhibition of the toll-like receptors (TLRs). The α7nAChR affects brain functions by modulating the function of neurons, glia, endothelial, immune, and dendritic cells and regulates inhibitory and excitatory neurotransmission throughout the GABA interneurons. In addition, Cotinine acting on the α7 nAChRs and TLR reduces neuroinflammation by inhibiting the release of pro-inflammatory cytokines by the immune cells. Also, α7nAChRs stimulate signaling pathways supporting structural, biochemical, electrochemical, and cellular changes in the Central nervous system during the cognitive processes, including Neurogenesis. Here, the mechanisms of memory formation as well as potential mechanisms of action of Cotinine on memory preservation in aging and neurological diseases are discussed.